THE INFLUENCE OF VITAMIN B6 ON CARDIAC OXIDATIVE STRESS, CARDIOMETABOLIC AND HISTOLOGICAL MARKERS IN MONOCROTALINE-INDUCED HEART FAILURE IN WISTAR ALBINO RATS - Jakovljevic Uzelac, Jovana (Medical Research, 2023)
AbstractHeart failure (HF) induced by monocrotaline (MCT) is well-known by the pulmonary arterial vessels remodeling mechanisms with increased pulmonary resistance and oxidative stress markers. The purpose of this study was to validate the hypothesis that treatment with vitamin B6 could affect HF by modulating cardiometabolic and oxidative stress biomarkers, and structure of the rat heart. The male Wistar albino rats were divided in 3 groups: blank solution-exposed control (C physiological saline 1ml/kg 28 days ip., n=8), B6 (vitamin B6 7mg/kg/day 28 days ip., n=8), and MCT+B6 (MCT 50mg/kg once ip. plus vitamin B6 7mg/kg/day 28 days ip., n=8). Four-week vitamin B6 treatment significantly affected certain biochemical parameters. The activity of key antioxidant enzymes, superoxide dismutase (SOD) and glutathione peroxidase (GPX) did not change, whereas the total glutathione (GSH) was significantly decreased in the MCT+B6 group. This was followed by slightly decreased level of the total glutathionylation observed in the MCT+B6 group. The parametres of protein oxidative damage (reactive carbonyl derivates, thiol groups and nitrotyrosine) did not significantly change in the MCT+B6 group. There was observed an increasing trend in RV and LV wall thickness in the MCT+B6 compared with the C group, as well as in Ki67 and PCNA positivity.  Key words: heart failure, monocrotaline, vitamin B6, oxidative stress, rat
Keywords: heart failure; monocrotaline; vitamin B6; oxidative stress; rat